Pengunaan Model Pembelajaran Kooperatif Tipe Jigsaw Untuk Meningkatkan Sikap Tanggung Jawab Siswa di Sekolah Dasar 64/I Muara Bulian - Widiya Apriliyani; Dwi Tyastuti; Laila Rahmasari; Syahrial Syahrial; Silvina Noviyanti (AS-SABIQUN, 2022)
The aim of the study was to determine the increase in students' responsible attitudes through the jigsaw type cooperative learning model in the fifth grade of SD Negeri 64/I Muara Bulian. This research is a classroom action research (CAR) which consists of two cycles, where the data taken is in the form of observation data through observation sheets of student responsibility attitudes and teacher observations using the jigsaw type cooperative learning model. This research was conducted in 4 stages, namely planning, implementation, observation and reflection. The results of this study showed an increase in the attitude of student responsibility as seen from the results of observations in the first cycle of student responsibility attitude of 39.28%. It increased in the second cycle to 74.77% with category B (good). Based on the findings of the research, it can be concluded that the attitude of students' responsibility in social studies learning for fifth grade students of SD Negeri 64/I Muara Bulian can increase after the jigsaw type cooperative learning model is applied.